Actualization and Modernization of History-Based Traditional Culinary for Preserving Surakarta Local Wisdom - Hermawan, Eko Satriya (The Indonesian Journal of Social Studies, 2022)
Indonesia is known for its wealth of local wisdom, among which local wisdom is a very diverse culinary treasure. Culinary is not only interpreted as food but has historical value, philosophy and identity of a society, but the current condition is sad because the fate of traditional culinary is marginalized and unpopular. This article will discuss the identification, explanation of the meaning and philosophy as well as the model of preserving the traditional culinary of Surakarta. To achieve the desired model, this research uses the qualitative method, then develops it in the form of a model. Articles from this research will have theoretical and practical contributions, especially for traditional culinary makers and lovers. The involvement of the general public, historians, practitioners and culinary business actors in this research will make the results obtained can be utilized and applied by stakeholders. From the data findings problem is first, starting from traditional culinary that is not raised in line with the changing times, so that it is equivalent to a variety of imported foods; Second, traditional culinary does not experience harmony and adjustment to the needs of modernist society; Third, the inherent backward connotation and relatively limited distribution; and Fourth, the lack of development and innovation carried out. Recognizing such problems, in this study, a model of the actualization and modernization of history-based traditional culinary was developed to preserve the local wisdom of Surakarta.